Basic conceptions of intrapersonal conflict. Theoretical and methodological research - Tymofiyeva Maryna Pylypivna (Studia Humanitatis, 2016)
The article analyses conceptions of intrapersonal conflict (IPC), identifies psychological characteristics of their manifestation and impact on an individual’s psychological health and professional development. The author reveals and analyses the psychoanalytic school’s views on the nature of IPC in. understanding the causes of inconsistencies between a person’s internal and external worlds we can both predict the occurrence of stress and crisis and prevent numerous conflicts.